River channel management : towards sustainable catchment hydrosystems - Downs, Peter W. (Peter William) (Arnold ; Distributed in the USA by Oxford University Press, 2004)
This is the first book to deal comprehensively with recent revolutions in river channel management. It explores the multidisciplinary nature of such management in relation to modern management techniques that bear the background of the entire drainage basin in mind, use channel restoration where appropriate, and are designed to be sustainable.